2017
DOI: 10.29122/jstmc.v18i1.2037
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Korelasi Kerapatan Titik Api Dengan Curah Hujan Di Pulau Sumatera Dan Kalimantan

Abstract: IntisariKebakaran hutan dan lahan merupakan bencana yang rutin terjadi di Indonesia. Pulau Sumatera dan Kalimantan menjadi wilayah yang paling sering dilanda kebakaran hutan dan lahan. Munculnya titik api di wilayah Sumatera dan Kalimantan mempunyai pola tersendiri. Penelitian ini bertujuan untuk mengetahui secara spasial-temporal konsentrasi titik api di wilayah Sumatera dan Kalimantan serta korelasinya dengan curah hujan. Berdasarkan hasil pengolahan data titik api yang bersumber dari hasil perekaman citra M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
(8 reference statements)
1
5
0
5
Order By: Relevance
“…In the DJF period (December January February) the density of hotspots in each grid is very low. This is in line with the results of Prayoga et al (2017). However, it can be seen that in this season, hotspots actually occur in low and moderate FWI classes.…”
Section: Conditional Probability Analysissupporting
confidence: 91%
“…In the DJF period (December January February) the density of hotspots in each grid is very low. This is in line with the results of Prayoga et al (2017). However, it can be seen that in this season, hotspots actually occur in low and moderate FWI classes.…”
Section: Conditional Probability Analysissupporting
confidence: 91%
“…A negative sign depicts the tendency for the hotspot to decline due to the increasing rainfall. Similar studies also reported a weak correlation (r = 0.307) between the hotspots and rainfalls in Sumatera and Kalimantan (Prayoga & Yananto, 2017). This outcome indicates that both variables do not linearly correlate as rainfall is not a single influencing factor of forest and land fires (Prasasti et al, 2012;Sitanggang et al, 2018).…”
Section: The Effects Of Rainfall On Hotspot In Tropical Regions Rainfall Forms An Important Climatic Consideration Thatmentioning
confidence: 82%
“…The daily distributions of hotspots and precipitation in September (Figure 2) show a strong negative correlation between them, where the number of hotspots increase in the absence of rain but are reduced or eliminated after measurable precipitation. Previous research has shown that the higher the monthly precipitation, the lower the number of monthly hotspots and vice versa [9]. Based on this analysis, it is assumed that the occurrence of forest and land fires in the HLG Sungai Buluh is mainly due to drought during the dry season, which is indicated by the low frequency and quantity of rainfall.…”
Section: Hotspot and Precipitationmentioning
confidence: 95%